Legal Pluralism based on World Policy Hybridization: A Comparison of Malaysian and Iranian Asset Forfeiture - Prasetya, Muhammad Djaelani; Ilyas, Amir; Arifin, Arnita Pratiwi; Fuady, Muhammad Ikram Nur; Saeedi, Yasin (Kosmik Hukum, 2026)
Asset forfeiture has developed into a global policy adopted by various countries as an instrument of corruption eradication. The United States and Australia already have asset forfeiture programs, as do countries in Asia. The direction is to strengthen the state to fight corrupt behaviors. This study analyzes the development of the contemporary criminalization of corruptors through a doctrinal comparative study of asset forfeiture policies in Iran and Malaysia. The results of the study showed that both countries adopted the policies of the United Nations Convention Against Corruption (UNCAC) and the recommendations of the Financial Action Task Force (FATF). Malaysia retains the influence of the British legal system with adjustments to customary law, while Iran implements a more revolutionary model through the practice of expanding sharia-based confiscation. In the Indonesian context, normative and institutional obstacles remain challenges, but implementation opportunities are open through the passage of the Asset Forfeiture Bill. This study recommends that the Bill regulate policies, mechanism models, proof, institutional, execution, and penal-non-penal practices, including the implementation of expanding confiscation. Thus, Indonesia can strengthen its anti-corruption regime through asset forfeiture instruments that are in line with international standards, the practices of other countries, and Indonesia's needs.